Hubungan Antara Persalinan Sectio Caesarea (SC) dan Kejadian Hipoglikemia Pada Neonatus di RSI Sultan Agung Semarang - Azizah Retno Kustiyah; Ayunda Wanda Hamida; Yulice Soraya Nur Intan (Journal of Midwifery and Health Science of Sultan Agung, 2023)
Introduction: Neonatal hypoglycemia is a condition in which newborn blood sugar levels are <47 mg/dL (2.61 mmol/L). Sectio casarea delivery has complications causing hypoglycemia in newborns, due to delays in initiation of early breastfeeding due to effect of sedation on postoperative mothers Sectio Caesarea (SC). In this study, to analyze the association between the sectio caesarea and its occurrence hypoglycemia in neonates at the Sultan Agung Islamic Hospital in Semarang. Methods: This research is analytic observational with cross Sectional design. The data used is secondary data in the form of medical records as many as 61 babies. The sampling technique in this study used purposive sampling. Sample data of 61 infants were analyzed on their blood sugar levels, if <47 mg/dl then it is called hypoglycemia, and >47mg/dL then it is called level normal sugar. Results: there were 16 neonates who experiencing hypoglycemia (GDS ≤ 47 mg/dl) with a percentage of 26.3% and 14 neonates with normal sugar levels (GDS > 47 mg/dl) with a percentage of 22.9%. A total of 5 neonates experienced hypoglycemia and 26 neonates with normal sugar levels by spontaneous manner. Conclusion: Based on the results of the study it can be concluded that there is a correlation which means between the method of delivery sectio caesarea with the occurrence hypoglycemia in neonates.